Vivien Allen, Lady Trader: A Biography of Mrs Sarah Heckford (Historia, 2021)
It took me three months to read this book and it is only 302 pages long. The problem with reading the biography of someone you have never heard of before picking up the book, is that you have no pre-existing affection for the subject to cushion the discovery of their less endearing traits. I found Sarah Heckford to be a person whom I'm very glad I did not know. She is one of those people who is very enthusiastic and helpful but extremely tiring. Her favourite adjective was "comical" and her zest for causes must have been exhausting. This said, the subject of Lady Trader demands reluctant respect. Sarah Heckford's life reflects the combined effects of strong personality, a love of adventure and challenge, and a stiff dose of "Rule Brittania" zeal. Filtered through Allen's somewhat unenlightened lens, this makes Lady Trader a worthwhile, if occasionally uncomfortable and exhaustingly dense, read.